The Effect of the Posterior Artificial Teeth Position on the Mobility of Lower Complete Dentures - Kawasaki, Takao; Nakakita, Yoshinobu; Yamamoto, Satoru; Mizuno, Kentarou; Notani, Kenji; Kakihara, Kensuke (Nihon Hotetsu Shika Gakkai Zasshi, 2001)
Purpose: To date, many researchers have reported arrangement methods for posterior artificial teeth. However, there are many unclear points concerning the effect of these arrangement methods on denture mobility. The purpose of this study was to obtain complete denture stability. This study was conducted to analyze three-dimensional behavior of lower complete dentures that have two posterior teeth arrangements, by a simulation method. Methods: We simulated two kinds of lower complete dentures and a mandibular edentulous model. We selected two posterior teeth arrangement methods: one based on the alveolar crest (A-denture), and the other was re-establishing the natural tooth position (N-denture). In a 50 N loading condition to the unilateral occlusal surface by changing the thickness of simulated food and the load position, we measured the displacement of dentures. Results: 1. In the loading condition to the unilateral, two lower complete dentures moved horizontally-protrusive-outward, the working side sunk, and the balancing side rose, even if we changed the thickness of the simulated food and the load position. 2. The displacement of lower complete dentures was influenced by the posterior teeth arrangement and the load position. The displacement of A-denture was less than that of N-denture, when compared in the difference between arrangement methods. Conclusions: The results of this study suggested that the mobility of an artificial teeth arrangement method based on the alveolar crest was less than that of a method of re-establishing the natural tooth position.